The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/app9214655
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Anaerobic Digestion of Lignocellulosic Wastes: Pretreatments and Operational Conditions

Abstract: Anaerobic digestion (AD) has become extremely popular in the last years to treat and valorize organic wastes both at laboratory and industrial scales, for a wide range of highly produced organic wastes: municipal wastes, wastewater sludge, manure, agrowastes, food industry residuals, etc. Although the principles of AD are well known, it is very important to highlight that knowing the biochemical composition of waste is crucial in order to know its anaerobic biodegradability, which makes an AD process economica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 163 publications
(228 reference statements)
0
30
0
1
Order By: Relevance
“…More VFAs will be produced in this condition, resulting in pH drop, and subsequently affecting the composition of ionized ammonia (NH4 + ) and free ammonia (NH3). In this case, free ammonia (NH3) is the direct inhibitor to the methanogens because of its high permeability to the cell membranes [19]. In this study, it was indicated that ammonia (NH3) did not severely affect biogas production, considering that the concentration still at an acceptable level (Fig.…”
Section: B the Dynamics Of Process Parametersmentioning
confidence: 71%
See 1 more Smart Citation
“…More VFAs will be produced in this condition, resulting in pH drop, and subsequently affecting the composition of ionized ammonia (NH4 + ) and free ammonia (NH3). In this case, free ammonia (NH3) is the direct inhibitor to the methanogens because of its high permeability to the cell membranes [19]. In this study, it was indicated that ammonia (NH3) did not severely affect biogas production, considering that the concentration still at an acceptable level (Fig.…”
Section: B the Dynamics Of Process Parametersmentioning
confidence: 71%
“…The turn-back pattern designates that the acidogenesis process will be gradually completed and followed by acetogenesis or methanogenesis. This pH turn-back is important since methanogenesis is reported to have optimum performance at the pH of 6.8-7.2 [17], [19]. The pH increase's ability may be determined by the alkalinity of the substrate/inoculum involved (adjusted) and the breakdown result of protein compounds.…”
Section: B the Dynamics Of Process Parametersmentioning
confidence: 99%
“…For this reason, it is possible that co-digestion with an additional substrate that has a higher C/N would be beneficial, as already demonstrated for other N-rich substrates (e.g., manure, slaughterhouse waste) [48,49].…”
Section: Resultsmentioning
confidence: 91%
“…TAN includes both NH 4 + and free ammonia (FAN, NH 3 ). FAN is the main cause of ammonia inhibition because it is membrane permeable [ 26 , 27 ]. So far, a FAN calculation method has rarely been applied in SS-AD, the digestate of which generally has a higher ionic strength than that in L-AD [ 23 ].…”
Section: Resultsmentioning
confidence: 99%